Outcomes from an elective medical student Research Scholarly Concentration program. (4th February 2019) - Radville, Laura; Aldous, Annette; Arnold, Jennifer; Hall, Alison K
Abstract : To examine how to increase research career outcomes among medical graduates, we analyzed the impact of the Research Scholarly Concentration at The George Washington University School of Medicine and Health Sciences. Residency placement, subsequent scholarship, and career outcomes were compared among 670 graduates who participated in the elective Clinical and Translational Research Scholarly Concentration or no Concentration between 2009 and 2018. We conducted a retrospective study of residency match (highly selective vs less selective), job type (academic vs non-academic), and postmedical school publications (any vs none). We compared the outcomes between Research Scholarly Concentration graduates and those with no Concentration, matched by graduation year (n=335). For Research Scholarly Concentration graduates, we examined the association between research outcomes and duration of research experience before medical school (n=232). Research Scholarly Concentration graduates were more likely to place in a highly selective residency (40.2% vs 21.6%, p<0.0001), 68% more likely to publish after medical school (OR=1.68, 95% CI 1.10 to 2.58), and almost four times as likely to have taken an academic health center job (OR=3.82, 95% CI 1.72 to 8.46) than graduates with no Concentration. Surprisingly, the length of research experience before medical school was not associated with these outcomes among Research Scholarly Concentration graduates. This suggests that a medical school Research Scholarly Concentration is effective in training physician researchers and should be available to both novices and research-experienced matriculants. These data suggest how other medical schools might plan Scholarly Concentration programs to improve research outcomes among medical graduates.